Effects of increased minimum wages by unemployment rate on suicide in the USA - Kaufman, John A (J Epidemiol Community Health, 2020)
BACKGROUND: Social welfare policies such as the minimum wage can affect population health, though the impact may differ by the level of unemployment experienced by society at a given time. METHODS: We ran difference-in-differences models using monthly data from all 50 states and Washington, DC from 1990 to 2015. We used educational attainment to define treatment and control groups. The exposure was the difference between state and federal minimum wage in US$2015, defined both by the date the state law became effective and lagged by 1 year. Models included state and year fixed effects, and additional state-level covariates to account for state-specific time-varying confounding. We assessed effect modification by the state-level unemployment rate, and estimated predicted suicide counts under different minimum wage scenarios. RESULTS: The effect of a US$1 increase in the minimum wage ranged from a 3.4% decrease (95% CI 0.4 to 6.4) to a 5.9% decrease (95% CI 1.4 to 10.2) in the suicide rate among adults aged 18–64 years with a high school education or less. We detected significant effect modification by unemployment rate, with the largest effects of minimum wage on reducing suicides observed at higher unemployment levels. CONCLUSION: Minimum wage increases appear to reduce the suicide rate among those with a high school education or less, and may reduce disparities between socioeconomic groups. Effects appear greatest during periods of high unemployment.